Kappa opioid receptors in the bed nucleus of the stria terminalis regulate binge-like alcohol consumption in male and female mice. (1st May 2020) - Haun, Harold L.; Griffin, William C.; Lopez, Marcelo F.; Becker, Howard C.
Abstract: Binge drinking is the most common pattern of excessive alcohol consumption and is a significant contributor to the development of Alcohol Use Disorder and dependence. Previous studies demonstrated involvement of kappa opioid receptors (KOR) in binge-like drinking in mice using the Drinking-in-the-Dark model. The current studies examined the role of KOR specifically in the bed nucleus of the stria terminals (BNST) in binge-like alcohol consumption in male and female mice. Direct administration of the long lasting KOR antagonist, nor-BNI, into the BNST decreased binge-like alcohol consumption and blood alcohol concentrations in male and female C57BL/6J mice. Similarly, direct nor-BNI administration into the BNST modestly reduced sucrose consumption and the suppression of fluid intake was not related to reduced locomotor activity. To further determine the role of KOR within the BNST on binge-like alcohol consumption, the KOR agonist U50, 488 was administered systemically which resulted in a robust increase in alcohol intake. Microinjection of nor-BNI into the BNST blocked the high level of alcohol intake after systemic U50, 488 challenge reducing intake and resultant blood alcohol concentrations. Together, these data suggest that KOR activity in the BNST contributes to binge-like alcohol consumption in both male and female mice. This article is part of the special issue on 'Neuropeptides'. Highlights: KOR antagonist in the BNST decreased binge-like alcohol consumption. KOR antagonist in the BNST modestly reduced binge-like sucrose consumption. KOR antagonist in the BNST does not affect locomotor activity. Systemic administration of a KOR agonist increased binge-like alcohol consumption. Effect of systemic KOR agonist was blocked by KOR antagonist in the BNST.